Measurement of Serum Stromelysin-2 Level in Iraqi Patients with Subclinical and Clinical Hypothyroidism - M. Ibraheem, Rand; A. Hamdi, Rana; M. Kadam, Satar (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Hypothyroidism is a medical condition characterized by increased levels of thyroid stimulating hormone and normal or decreased levels of thyroid hormones. This condition may contribute to dyslipidemia, hypertension, atherosclerosis, cognitive impairment, neuromuscular dysfunction and infertility. Several factors that increase the risk of cardiovascular disease, such as metabolic syndrome and dyslipidemia, are related to obesity. Stromelysin-2, also known as matrix metalloproteinase-10, is an enzyme produced by cells that breaks down the extracellular matrix in various tissues, including blood vessels. Objective: To assess the levels of serum stromelysin-2 in patients with subclinical and clinical hypothyroidism and compare them with healthy controls. Additionally, to determine the relationship between serum stromelysin-2 levels and the anthropometric measures. Methods: A case control study was conducted with 130 Iraqi individuals divided into three groups. The study aimed to measure serum stromelysin-2 and anthropometric parameters such as body mass index, waist circumference, and waist-to-hip ratio. To differentiate between more than two independent means the ANOVA test was used for blood investigations. Result: The study found that clinical and subclinical hypothyroid patients had significant higher mean body mass index (P = 0.001), waist circumference (P = 0.001), waist to hip ratio (P = 0.001), and serum stromelysin-2 (P = 0.001) compared to healthy control. Among patients with clinical hypothyroidism group, there were positive correlations between serum stromelysin-2 and body mass index (r = 0.413, p = 0.005), waist circumference (r = 0.406, p = 0.006), and waist to hip ratio (r = 0.367, p = 0.013). Conclusion: It has been observed that patients suffering from clinical and subclinical hypothyroid patients tend to have a higher body weight, as measured by their body mass index, waist circumference, and waist-to-hip ratio. This may indicate an increased risk of cardiovascular disease. Additionally, such patients have been found to have high levels of stromelysin-2, a protein that is believed to be indicative of early atherosclerosis in blood vessels. This suggests that stromelysin-2 could potentially be used as a marker for predicting cardiovascular disease in hypothyroid patients.